Digital marketing strategy and implementation of multi-channels for traditional retail - Surahman Surahman; Sugeng Hariyadi; Bela Barus; Rif’ah Rif’ah; Sarlivia Sarlivia; Riza Meidinata; Desi Kartina (Community Empowerment, 2023)
This Community Service (PkM) aims to provide an understanding of the development of information technology related to digital marketing. This PkM Partnership was carried out by collaborating with the traditional retail store Anggun. Activities were carried out through socialization, training, mentoring, and website dissemination. Digital marketing strategies and multi-channel implementation were disseminated in the form of e-commerce websites and multi-channel applications. In addition to that, the Buku Warung non-cash payment system and the Indonesian Standard Quick Response Code (QRIS) were also introduced. The result of this activity was an increase in sales turnover in the last three months by 69.73%.